SCR Catalyst

By adding antimony oxide to the vanadium-based SCR catalyst, the composition of the catalyst is optimized, and the problem of reduced activity of the catalyst in the case of excessive NO2 and NO and insufficient activity of the low temperature is solved, and a more efficient and stable nitrogen oxide conversion effect is achieved.

CN116474763BActive Publication Date: 2025-04-04UMICORE AG & CO KG
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310531105.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-11-14
Filing Date
2018-11-13
Publication Date
2025-04-04
Estimated Expiration
2038-11-13

AI Technical Summary

Technical Problem

The existing vanadium-based SCR catalysts have reduced activity in the case of excessive NO2 and excessive NO, and have insufficient low-temperature activity, and the thermal stability needs to be improved.

Method used

The composition of the catalyst is optimized by adding antimony oxide to the vanadium-based SCR catalyst containing cerium oxide, including 2 to 6 wt% vanadium oxide oxide, 0.5 to 2 wt% of tungsten oxide, 2 to 4 wt% of cerium oxide, 1 to 7 wt% of antimony oxide and measured titanium oxide.

Benefits of technology

It is achieved to maintain good activity under the conditions of excessive NO2 and excessive NO, especially at low temperature conditions (T<250°C), while improving the thermal stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116474763B_ABST
    Figure CN116474763B_ABST
Patent Text Reader

Abstract

The invention relates to an SCR catalyst, and an exhaust gas system containing said oxide, said catalyst comprising at least one oxide of vanadium, at least one oxide of tungsten, at least one oxide of cerium, at least one oxide of titanium and at least one oxide of antimony.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This divisional application is a divisional application based on the Chinese patent application with application number 201880074011.0, application date November 13, 2018, and invention name “SCR Catalyst”. Technical Field

[0002] The present invention relates to a vanadium oxide-based SCR catalyst containing antimony oxide and cerium oxide. Background Art

[0003] Exhaust gas removal of carbon monoxide (CO) and nitrogen oxides (NO x ) also contain components resulting from incomplete combustion of the fuel in the combustion chamber of the cylinder. In addition to residual hydrocarbons (HC), which are usually also present mainly in gaseous form, these components also include particulate emissions. These particulate emissions are complex agglomerates mainly from carbonaceous particles and an adhering liquid phase, which usually mainly contains long-chain hydrocarbon condensates. The liquid phase adhering to the solid components is also called "soluble organic fraction SOF" or "volatile organic fraction VOF".

[0004] In order to clean such exhaust gases, the above-mentioned components must be converted as completely as possible into harmless compounds, which is only possible through the use of suitable catalysts.

[0005] A well-known process for removing nitrogen oxides from exhaust gases in the presence of oxygen is the selective catalytic reduction (SCR process) using ammonia on a suitable catalyst. With this process, the nitrogen oxides to be removed in the exhaust gases are converted into nitrogen and water using ammonia as a reducing agent.

[0006] The so-called "standard SCR reaction" according to formula (I)

[0007] NH3+NO+1 / 4O2→N2+3 / 2H2O(I)

[0008] and the so-called "fast SCR reaction" according to formula (II)

[0009] NH3+1 / 2NO+1 / 2NO2→N2+3 / 2H2O(II)

[0010] It is considered to be an important reaction pathway of SCR reaction.

[0011] Since the exhaust gas of a lean combustion engine usually contains only NO2 in an amount of about 10% of the total nitrogen oxide proportion, it is often desirable to increase its amount in order to benefit from a fast SCR reaction. This is done, for example, by an upstream oxidation catalytic converter. However, depending on the exhaust system used in the specific case, the SCR catalyst may still be faced with very different NO2 / NOx ratios, which can range from excessive NO to excessive NO2.

[0012] Ammonia used as reducing agent can be made available by dosing an ammonia precursor compound such as urea, ammonium carbamate or ammonium formate into the exhaust gas line and subsequently hydrolyzing it.

[0013] So-called mixed oxide catalysts, which are based on vanadium oxides and generally also contain titanium oxides and oxides of further metals, such as tungsten oxides, can also be used as SCR catalysts (see Isabella Nova and Enrico Tronconi (eds.), Urea-SCR Technology for deNOx After Treatment of Diesel Exhausts, Chapter 3, Springer Verlag, 2014).

[0014] If the nitrogen oxides contained in the exhaust gas are present in the form of NO or at least predominantly in the form of NO, SCR catalysts based on vanadium oxide are characterized by good activity and stability. However, in the case of an excess of NO2, they show a significant decrease in activity. Although the addition of cerium oxide to SCR catalysts based on vanadium oxide increases the activity in the case of an excess of NO2, it also impairs the low-temperature activity (T<250°C) in the case of an excess of NO.

[0015] Therefore, there is a need for vanadium oxide based SCR catalysts that have good activity for both NO2 excess and NO excess and low temperature (T<250°C). In addition, there is a need to improve the thermal stability of vanadium based SCR catalysts.

[0016] It is also known to use antimony oxide in SCR catalysts based on metal oxides. Thus, for example, US 9,662,610 discloses a method for reducing nitrogen oxides using a catalyst comprising titanium dioxide, a vanadium compound and an antimony compound. WO2017 / 101449 A1 discloses the use of a catalyst composition comprising titanium dioxide, a composite oxide containing vanadium and antimony and optionally oxides of silicon, vanadium and antimony.

[0017] CN106215929 discloses a cerium antimony composite oxide used as a denitrification catalyst.

[0018] Finally, US 8,975,206 discloses catalyst compositions which, in addition to vanadium and titanium, may also contain antimony. Summary of the invention

[0019] It has now surprisingly been found that, starting from a vanadium oxide-based SCR catalyst containing cerium oxide, the above-mentioned technical problem can be solved by adding antimony oxide to the catalyst.

[0020] Therefore, the present invention relates to a catalyst comprising

[0021] at least one oxide of vanadium in an amount of 2% to 6% by weight,

[0022] at least one tungsten oxide in an amount of 0.5% to 2% by weight,

[0023] at least one cerium oxide in an amount of 2% to 4% by weight,

[0024] at least one antimony oxide in an amount of 1% to 7% by weight,

[0025] as well as

[0026] · at least one oxide of titanium in an amount measured so as to give a total of 100% by weight,

[0027] In each case this is based on the total weight of the catalyst and calculated as V2O5, WO3, CeO2, Sb2O5 or TiO2.

[0028] The at least one titanium oxide serves as support material, the at least one vanadium oxide serves as active catalyst component, and the at least one tungsten, cerium and antimony oxide serves as promoter. Promoter is understood to mean a substance which maintains or increases the activity of the catalyst.

[0029] In one embodiment of the catalyst according to the invention, it additionally contains at least one silicon oxide.

[0030] In a further embodiment of the catalyst according to the invention, it additionally contains at least one oxide of molybdenum, niobium, zirconium, tantalum and / or hafnium.

[0031] In a preferred embodiment of the catalyst according to the invention, it contains at least one cerium oxide in an amount of 2% to 4% by weight, relative to the weight of the catalyst and calculated as CeO2. In a further preferred embodiment of the catalyst according to the invention, it contains at least one antimony oxide in an amount of 1% to 7% by weight, relative to the weight of the catalyst and calculated as Sb2O5. Furthermore, preference is given to embodiments of the catalyst according to the invention which contain at least one cerium oxide in an amount of 2% to 4% by weight, calculated as CeO2, and at least one antimony oxide in an amount of 1% to 7% by weight, calculated as Sb2O5, in each case based on the weight of the catalyst.

[0032] In a further preferred embodiment of the catalyst according to the invention, it contains

[0033] at least one oxide of vanadium in an amount of 2% to 6% by weight,

[0034] at least one tungsten oxide in an amount of 0.5% to 2% by weight,

[0035] at least one cerium oxide in an amount of 2% to 4% by weight,

[0036] at least one antimony oxide in an amount of 1% to 7% by weight, and

[0037] · at least one oxide of titanium in an amount measured so as to give a total of 100% by weight,

[0038] This is in each case based on the total weight of the catalyst and calculated as V2O5, WO3, CeO2 or Sb2O5.

[0039] If the catalyst according to the invention contains at least one silicon oxide, it is preferably present in an amount of 2% to 7% by weight, relative to the weight of the catalyst and calculated as SiO2.

[0040] If the catalyst according to the invention contains at least one oxide of molybdenum, niobium, zirconium, tantalum and / or hafnium, the total amount of these oxides is preferably from 0.5% to 20% by weight, relative to the weight of the catalyst and calculated as MoO3, Nb2O5, ZrO2, Ta2O5 or HfO2.

[0041] The catalyst according to the invention preferably contains no magnesium or magnesium compounds.

[0042] In another embodiment, the catalyst of the present invention also contains no zirconium or zirconium compounds.

[0043] In the context of the present invention, the term vanadium oxides includes all oxides which are present or may be present under the conditions of preparation, storage and use of the catalyst according to the invention. Thus, it includes, for example, V2O5, but also all other vanadium oxides.

[0044] Similarly, the term tungsten oxide includes, for example, WO3, but also includes all other oxides of tungsten, the term cerium oxide includes, for example, CeO2, but also includes all other oxides of cerium, the term antimony oxide includes, for example, Sb2O5, but also includes all other oxides of antimony, the term titanium oxide includes, for example, TiO2, but also includes all other oxides of titanium, and silicon oxide includes, for example, SiO2, but also includes all other oxides of silicon. The same is true for the terms molybdenum, niobium, zirconium, tantalum and hafnium oxides.

[0045] The catalyst according to the invention can be produced in a simple manner.

[0046] Thus, for example, the oxides of vanadium, tungsten, cerium, antimony and titanium and optionally other metal oxides can be thoroughly mixed in powder form in the desired amounts and then calcined. However, it is generally advantageous to slurry the aforementioned oxides in water and then dry and calcine.

[0047] In a variant of the method, initially only a portion of the metal oxide is provided, while the remaining metal is added in the form of a water-soluble metal salt. For example, oxides of tungsten, cerium, antimony and titanium can be provided, which are then impregnated with an aqueous solution of a water-soluble vanadium compound, then dried and calcined. Suitable water-soluble vanadium compounds are particularly vanadium oxalate, which can be obtained by dissolving vanadium pentoxide in oxalic acid (see, for example, EP 0 345 695 A2) or by the reaction product of vanadium pentoxide with an amine or ethanolamine (see, for example, WO 89 / 03366A1 and WO 2011 / 013006), especially ammonium metavanadate. DE 112007 000 814T5 also describes the use of vanadium trichloride.

[0048] Alternatively, oxides of vanadium, cerium, antimony and titanium can also be provided and then impregnated with an aqueous solution of a water-soluble tungsten compound, followed by drying and calcination. A suitable water-soluble tungsten compound for this purpose is ammonium metatungstate.

[0049] Instead of using individual oxides, two or more metal oxides can also be used in the form of corresponding mixed oxides or in the form of metal oxides doped with one or more other metal oxides. For example, titanium dioxide doped with silicon dioxide and tungsten trioxide can be impregnated with water-soluble compounds of vanadium and antimony, then dried and calcined.

[0050] Depending on the production method, the catalyst according to the invention may be present in the form of a mixture of metal oxides, a mixed oxide, but in particular in the form of an intermediate between a mixture of metal oxides and a mixed oxide. For example, two or three metals may be present in the form of a mixed oxide impregnated with the remaining metals.

[0051] The starting compounds required for the preparation of the catalysts according to the invention, such as metal oxides, mixed oxides or water-soluble metal salts, are known to the person skilled in the art and are commercially available.

[0052] In a preferred embodiment, the catalyst according to the invention is present as a coating on a support body which can be present as a flow-through honeycomb body or as a wall-flow filter.

[0053] In embodiments of the invention, the support body is catalytically inert and consists of a ceramic or metallic material, such as silicon carbide, aluminum titanate or cordierite. In these embodiments, all components of the catalyst according to the invention are present in one coating.

[0054] The coated support bodies can be produced according to methods familiar to the person skilled in the art, for example according to customary dip-coating methods or pump- and suction-coating methods with subsequent thermal aftertreatment (calcination).

[0055] In a further embodiment of the present invention, the catalyst according to the invention itself is a component of a support body, in which case the support body is formed by the catalyst according to the invention and a matrix component.

[0056] Support bodies, flow-through substrates and wall-flow substrates which consist not only of inert materials such as cordierite but also additionally contain catalytically active materials are known to the person skilled in the art. To prepare them, a mixture consisting of, for example, 10 to 95% by weight of an inert matrix component and 5 to 90% by weight of a catalytically active material is extruded according to methods known per se. In this case, all inert materials which are also used for the production of catalyst substrates can be used as matrix components. These are, for example, silicates, oxides, nitrides or carbides, with magnesium aluminum silicate being particularly preferred.

[0057] The catalyst according to the invention is particularly suitable for reducing nitrogen oxides in the exhaust gases of lean-burn internal combustion engines, in particular diesel engines.

[0058] The present invention therefore also relates to a method for reducing nitrogen oxides in the exhaust gas of a lean-burn internal combustion engine, the method comprising the following method steps:

[0059] - adding a reducing agent to said exhaust gas containing nitrogen oxides, and

[0060] The resulting mixture from the exhaust gas containing nitrogen oxides and the reducing agent is passed over the catalyst according to the invention.

[0061] As reducing agent, ammonia is particularly considered due to its specific advantages, not ammonia itself but an ammonia precursor, in particular urea, being added to the exhaust gas containing nitrogen oxides.

[0062] In particular, the catalyst according to the invention is used as a component of an exhaust gas cleaning system which, in addition to the catalyst according to the invention, comprises, for example, an oxidation catalyst and a diesel particulate filter arranged on the inflow side. In this way, the catalyst according to the invention can also be present as a coating on the diesel particulate filter.

[0063] Therefore, the present invention also relates to an exhaust gas purification system for treating exhaust gas from a diesel engine, the exhaust gas purification system comprising, in the flow direction of the exhaust gas:

[0064] - oxidation catalyst,

[0065] - Diesel particulate filter, and

[0066] - a catalyst according to the invention,

[0067] or

[0068] - Oxidation catalyst and

[0069] A diesel particle filter on which the catalyst according to the invention is present as a coating.

[0070] Oxidation catalysts (in particular platinum, palladium, or platinum and palladium supported, for example, on alumina) and diesel particulate filters suitable for the exhaust gas purification system according to the invention are known to the person skilled in the art and are commercially available.

[0071] The exhaust gas purification system according to the invention generally comprises a device for metering a reducing agent, which is arranged upstream of the catalyst according to the invention.

[0072] The injection device can be selected arbitrarily by the person skilled in the art, wherein suitable devices can be obtained from the literature (see, for example, T. Mayer, Feststoff-SCR-System auf Basis von Ammonium-carbamat, Dissertation, Technical University of Kaiserslautern, 2005). The reducing agent introduced into the exhaust gas stream via the injection device can be in particular ammonia itself or in the form of a compound from which ammonia is formed under ambient conditions. Examples of suitable compounds are aqueous solutions of urea or ammonium formate and solid ammonium carbamate. In general, the reducing agent or its precursor is stored in a container associated with the injection device and connected to the injection device.

[0073] Specifically, the present invention provides the following technical solutions:

[0074] Item 1. A catalyst comprising

[0075] at least one oxide of vanadium in an amount of 2% to 6% by weight,

[0076] at least one tungsten oxide in an amount of 0.5% to 2% by weight,

[0077] at least one cerium oxide in an amount of 2% to 4% by weight,

[0078] at least one antimony oxide in an amount of 1% to 7% by weight,

[0079] as well as

[0080] · Amounts of at least one titanium oxide measured so as to give a total of 100% by weight, based in each case on the total weight of the catalyst and calculated as V2O5, WO3, CeO2, Sb2O5 or TiO2.

[0081] Item 2. The catalyst according to Item 1, characterized in that the catalyst contains at least one silicon oxide.

[0082] Item 3. The catalyst according to Item 1 and / or 2, characterized in that the catalyst contains at least one oxide of molybdenum, niobium, zirconium, tantalum and / or hafnium.

[0083] Item 4. A catalyst according to one or more of Items 1 to 3, characterized in that the catalyst contains 2 wt% to 7 wt% of at least one silicon oxide, based on the total weight of the catalyst and calculated as SiO2.

[0084] Item 5. A catalyst according to any one of Items 1 to 4, characterized in that the catalyst contains at least one oxide of molybdenum, niobium, zirconium, tantalum and / or hafnium, and the total amount of these oxides is 0.5 weight % to 20 weight % based on the total weight of the catalyst and calculated as MoO3, Nb2O5, ZrO2, Ta2O5 or HfO2.

[0085] Item 6. The catalyst according to any one of Items 1 to 5, characterized in that the catalyst is present as a coating on a carrier body.

[0086] Item 7. The catalyst according to any one of Items 1 to 6, characterized in that the catalyst exists as part of a support body.

[0087] Item 8. A method for reducing nitrogen oxides in the exhaust gas of a lean-burn internal combustion engine, comprising the following method steps

[0088] - adding a reducing agent to said exhaust gas containing nitrogen oxides, and

[0089] - passing the resulting mixture of exhaust gas containing nitrogen oxides and reducing agent over a catalyst according to any one of items 1 to 7.

[0090] Item 9. An exhaust gas purification system for treating exhaust gas from a diesel engine, comprising:

[0091] - oxidation catalyst,

[0092] - Diesel particulate filter, and

[0093] - a catalyst according to any one of items 1 to 7,

[0094] or

[0095] - Oxidation catalyst and

[0096] - A diesel particulate filter, on which the catalyst according to any one of items 1 to 6 is present as a coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0097] The present invention is explained in more detail below by means of the accompanying drawings and examples. The following are shown:

[0098] Figure 1 : Nitrogen oxide conversion in the standard SCR reaction measured on the catalysts K1 and K7 according to the invention in the fresh state in comparison with the comparative catalysts VK1, VK2, VK3 and VK4 (K1f, VK1f, VK2f, VK3f, VK4f and K7f).

[0099] Figure 2 : Nitrogen oxide conversion in the standard SCR reaction measured on the catalysts K1 and K7 according to the invention in the aged state in comparison with the comparative catalysts VK1, VK2, VK3 and VK4 (K1a, VK1a, VK2a, VK3a, VK4a and K7a).

[0100] Figure 3 : Nitrogen oxide conversion in the fast SCR reaction measured on the catalysts K1 and K7 according to the invention in the fresh state in comparison with the comparative catalysts VK1, VK2, VK3 and VK4 (K1f, VK1f, VK2f, VK3f, VK4f and K7f).

[0101] Figure 4 : Nitrogen oxide conversion in the fast SCR reaction measured on the catalysts K1 and K7 according to the invention in the aged state in comparison with the comparative catalysts VK1, VK2, VK3 and VK4 (K1a, VK1a, VK2a, VK3a, VK4a and K7a).

[0102] Figure 5 : Nitrogen oxide conversion relative to the WO3 content in the standard SCR reaction at 200° C. and in the fast SCR reaction at 300° C. measured on the catalysts K1, K2 and K3 according to the invention in the new and aged state in comparison with the comparative catalyst VK4.

[0103] Figure 6 : Nitrogen oxide conversion relative to the CeO2 content in the standard SCR reaction at 200° C. and in the fast SCR reaction at 300° C. measured on the catalysts K1 and K4 according to the invention in the new and aged state in comparison with the comparative catalyst VK3.

[0104] Figure 7 : Nitrogen oxide conversion relative to the Sb2O5 content in the standard SCR reaction at 200° C. and in the fast SCR reaction at 300° C. measured on the catalysts K1, K5 and K6 according to the invention in the new and aged state in comparison with the comparative catalyst VK2. DETAILED DESCRIPTION

[0105] Example 1

[0106] a) Commercially available titanium dioxide in the form of anatase doped with 5 wt% silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2) and antimony pentoxide (Sb2O5) were added to obtain a catalyst having a composition of 86.00 wt% TiO2, 4.50 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3, 2.00 wt% CeO2 and 2.75 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0107] b) The dispersion obtained according to a) was applied in a conventional manner to a commercially available ceramic flow substrate having a volume of 0.5 L, a pore number of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst K1 thus obtained was present in the fresh state and is therefore referred to hereinafter as K1f.

[0108] c) Catalyst K1 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O, balance N 2 ). Catalyst K1 was then present in the aged state and is referred to hereinafter as K1a.

[0109] Comparative Example 1

[0110] a) dispersing a commercially available titanium dioxide in the form of anatase doped with 5 wt. % silicon dioxide in water, and then adding a certain amount of vanadium dioxide (VO2) and tungsten trioxide (WO3) so as to obtain a composition of 90.5 wt. % TiO2, 4.75 wt. % SiO2,

[0111] 3.75 wt% V2O5, 1.00 wt% WO3 catalyst. The slurry was stirred vigorously and then ground in a commercially available stirred sand mill.

[0112] b) coating the dispersion obtained according to a) in a conventional manner on a commercially available ceramic flow substrate having a volume of 0.5 L and a pore number of 62 pores per square centimeter,

[0113] The wall thickness over its entire length was 0.17 mm and the washcoat loading was 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst VK1 thus obtained was present in the fresh state and is therefore referred to below as VK1f. c) VK1 obtained according to b) was heated at 700° C. in a gas atmosphere (10% O2, 10% H2O,

[0114] The remainder was subjected to hydrothermal aging for 48 hours in N2. Catalyst VK1 was then present in the aged state and is referred to hereinafter as VK1a.

[0115] Comparative Example 2

[0116] a) dispersing a commercially available titanium dioxide in the form of anatase doped with 5 wt. % silicon dioxide in water, and then adding a certain amount of vanadium dioxide (VO2), tungsten trioxide (WO3) and cerium dioxide (CeO2) so as to obtain a composition of 88.60 wt. % TiO2,

[0117] 4.65 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3 and 2.00 wt%

[0118] The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0119] b) The dispersion obtained according to a) was coated in a conventional manner on a commercially available ceramic flow-through substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length, and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours.

[0120] The catalyst VK2 obtained is in the fresh state and is therefore referred to below as VK2f. c) The VK2 obtained according to b) is heated at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O,

[0121] The remainder was subjected to hydrothermal aging for 48 hours in N2. Catalyst VK2 was then present in the aged state and is referred to hereinafter as VK2a.

[0122] Comparative Example 3

[0123] a) A commercially available anatase-form titanium dioxide doped with 5 wt% silicon dioxide was dispersed in water, and then a certain amount of vanadium dioxide (VO2), tungsten trioxide (WO3) and antimony pentoxide was added to obtain a catalyst with a composition of 87.9 wt% TiO2, 4.60 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3 and 2.75 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0124] b) The dispersion obtained according to a) was coated in a conventional manner on a commercially available ceramic flow-through substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length, and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours.

[0125] The catalyst VK3 obtained is in the fresh state and is therefore referred to below as VK3f. c) The VK3 obtained according to b) is heated at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O,

[0126] The remainder was subjected to hydrothermal aging for 48 hours in N2). Catalyst VK3 was then present in the aged state and is referred to hereinafter as VK3a.

[0127] Comparative Example 4

[0128] a) A commercially available titanium dioxide in the form of anatase doped with 5 wt. % silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), cerium dioxide (CeO2) and antimony pentoxide were added to obtain a composition of 86.9 wt. % TiO2, 4.60

[0129] wt% SiO2, 3.75 wt% V2O5, 2.00 wt% CeO2 and 2.75 wt%

[0130] The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0131] b) The dispersion obtained according to a) was coated in a conventional manner on a commercially available ceramic flow-through substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length, and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours.

[0132] The catalyst VK4 obtained is in the fresh state and is therefore referred to below as VK4f. c) The VK4 obtained according to b) is heated at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O,

[0133] The remainder was subjected to hydrothermal aging for 48 hours in N2. Catalyst VK4 was then present in the aged state and is referred to hereinafter as VK4a.

[0134] Example 2

[0135] a) Commercially available titanium dioxide in the form of anatase doped with 5 wt% silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2) and antimony pentoxide (Sb2O5) were added to obtain a catalyst having a composition of 86.45 wt% TiO2, 4.55 wt% SiO2, 3.75 wt% V2O5, 0.50 wt% WO3, 2.00 wt% CeO2 and 2.75 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0136] b) The dispersion obtained according to a) was applied in a conventional manner to a commercially available ceramic flow substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst K2 thus obtained was present in the fresh state and is therefore referred to hereinafter as K2f.

[0137] c) K2 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O2, 10% H2O, balance N2). Catalyst K2 was then present in the aged state and is referred to hereinafter as K2a.

[0138] Example 3

[0139] a) Commercially available titanium dioxide in the form of anatase doped with 5 wt% silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2) and antimony pentoxide (Sb2O5) were added to obtain a catalyst having a composition of 85.03 wt% TiO2, 4.47 wt% SiO2, 3.75 wt% V2O5, 2.00 wt% WO3, 2.00 wt% CeO2 and 2.75 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0140] b) The dispersion obtained according to a) was applied in a conventional manner to a commercially available ceramic flow substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst K3 thus obtained was present in the fresh state and is therefore referred to hereinafter as K3f.

[0141] c) K3 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O, balance N 2 ). Catalyst K3 was then present in the aged state and is referred to hereinafter as K3a.

[0142] Example 4

[0143] a) Commercially available titanium dioxide in the form of anatase doped with 5 wt% silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2) and antimony pentoxide (Sb2O5) were added to obtain a catalyst having a composition of 84.07 wt% TiO2, 4.43 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3, 4.00 wt% CeO2 and 2.75 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0144] b) coating the dispersion obtained according to a) in a conventional manner on a commercially available ceramic flow substrate having a volume of 0.5 L and a pore number of 62 pores per square centimeter,

[0145] The wall thickness over its entire length was 0.17 mm, the washcoat loading was 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst K4 thus obtained was present in the fresh state and is therefore referred to below as K4f.

[0146] c) K4 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O, balance N 2 ). Catalyst K4 was then present in the aged state and is referred to hereinafter as K4a.

[0147] Example 5

[0148] a) Commercially available titanium dioxide in the form of anatase doped with 5 wt% silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2) and antimony pentoxide (Sb2O5) were added to obtain a catalyst having a composition of 84.79 wt% TiO2, 4.46 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3, 2.00 wt% CeO2 and 4.00 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0149] b) The dispersion obtained according to a) was applied in a conventional manner to a commercially available ceramic flow substrate having a volume of 0.5 L, a pore number of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst K5 thus obtained was present in the fresh state and is therefore referred to hereinafter as K5f.

[0150] c) K5 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O, balance N 2 ). Catalyst K5 was then present in the aged state and is referred to hereinafter as K5a.

[0151] Example 6

[0152] a) Commercially available titanium dioxide in the form of anatase doped with 5 wt% silicon dioxide was dispersed in water, and then certain amounts of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2) and antimony pentoxide (Sb2O5) were added to obtain a catalyst having a composition of 81.94 wt% TiO2, 4.31 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3, 2.00 wt% CeO2 and 7.00 wt% Sb2O5. The slurry was vigorously stirred and then ground in a commercially available stirred sand mill.

[0153] b) The dispersion obtained according to a) was applied in a conventional manner to a commercially available ceramic flow substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length and a washcoat loading of 360 g / L. The powder thus obtained was dried at 90° C. and then calcined at 600° C. for 2 hours. The catalyst K6 thus obtained was present in the fresh state and is therefore referred to hereinafter as K6f.

[0154] c) K6 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O, balance N 2 ). Catalyst K6 was then present in the aged state and is referred to hereinafter as K6a.

[0155] Example 7

[0156] a) Dispersing commercially available anatase titanium dioxide in water, and then adding a certain amount of vanadium dioxide (VO2), tungsten trioxide (WO3), cerium dioxide (CeO2)

[0157] and antimony pentoxide (Sb2O5) to obtain a catalyst having a composition of 90.5 wt% TiO2, 3.75 wt% V2O5, 1.00 wt% WO3, 2.00 wt% CeO2 and 2.75 wt% Sb2O5. The slurry was stirred vigorously and then ground in a commercially available stirred sand mill.

[0158] b) The dispersion obtained according to a) was coated in a conventional manner on a commercially available ceramic flow substrate having a volume of 0.5 L, a pore count of 62 pores per square centimeter, a wall thickness of 0.17 mm over its entire length, and a washcoat loading of 360 g / L.

[0159] The powder thus obtained was dried at 90° C. and then calcined for 2 hours at 600° C. The catalyst K7 thus obtained was present in the fresh state and is therefore referred to below as K7f.

[0160] c) K7 obtained according to b) was subjected to hydrothermal aging for 48 hours at 700° C. in a gas atmosphere (10% O 2 , 10% H 2 O, balance N 2 ). Catalyst K7 was then present in the aged state and is referred to hereinafter as K7a.

[0161] The compositions of the catalysts of the examples are summarized in Table 1. The compositions of the catalysts according to the invention are not limited to the explicitly shown examples.

[0162] Table 1: Composition of the catalysts of the examples

[0163]

[0164] Determination of the nitrogen oxide conversion rate as a measure of SCR activity:

[0165] The NO conversion of the catalysts prepared according to the above examples and comparative examples or comparative catalysts was determined in a quartz glass reactor. Drill cores with L=3" and D=1" were tested between 200°C and 400°C under steady-state conditions. The tests were carried out in a laboratory model gas system under the following conditions.

[0166]

[0167] During the measurement, the nitrogen oxide concentration of the model gas after the flow through the catalyst is recorded using a suitable analytical method. From the known, metered nitrogen oxide content (verified during the conditioning period using a pre-catalyst exhaust gas analysis at the start of the respective test flow) and the nitrogen oxide conversion content measured after the flow through the catalyst, the nitrogen oxide conversion relative to the ratio of NH3 to NO at each temperature measurement point on the catalyst is calculated as follows:

[0168]

[0169] in

[0170] c 输入 / 输出 (NO x )=c 输入 / 输出 (NO)+c 输入 / 输出 (NO2)+c 输入 / 输出 (N2O)

[0171] The obtained nitrogen oxide conversion rate value U NOx [%] is plotted as a function of the temperature measured before the catalyst in order to assess the SCR activity of the investigated materials.

[0172] Table 2 shows the NOx conversion rates of the above examples in a standard SCR reaction.

[0173] Table 2: NOx conversion in standard SCR reactions

[0174]

[0175] The results of the standard SCR reaction of the new catalyst are Figure 1 Shown in.

[0176] The results of the standard SCR reaction of the aged catalyst are Figure 2 Shown in.

[0177] Table 3 shows the NOx conversion rates of the above examples in the fast SCR reaction.

[0178] Table 3: NOx conversion in fast SCR reaction

[0179]

[0180] The results of the fast SCR reaction of the new catalyst are Figure 3 Shown in.

[0181] The result of the fast SCR reaction of the aged catalyst is Figure 4 Shown in.

[0182] Table 4 shows the effect of the WO3 content of the catalyst on the NOx conversion in the standard SCR reaction at 200° C. and in the fast SCR reaction at 300° C. in the new and aged state. The amount of V2O5, CeO2 and Sb2O5 was kept constant at 3.75 wt%, 2.00 wt% or 2.75 wt%, respectively, while the WO3 content was varied from 0.00 wt% (VK4) to 0.50 wt% (K2), 1.00 wt% (K1) and 2.00 wt% (K3).

[0183] Table 4: Effect of WO3 content on NOx conversion rate

[0184]

[0185] The results of the influence of WO3 content are Figure 5 Shown in.

[0186] Table 5 shows the effect of the CeO2 content of the catalyst on the NOx conversion in the standard SCR reaction at 200° C. and in the fast SCR reaction at 300° C. in the new and aged state. The amounts of V2O5, WO3 and Sb2O5 were kept constant at 3.75 wt%, 1.00 wt% or 2.75 wt%, respectively, while the CeO2 content was varied from 0.00 wt% (VK3) to 2.00 wt% (K1) and 2.00 wt% (K7).

[0187] Table 5: Effect of CeO2 content on NOx conversion rate

[0188]

[0189] The results of the influence of CeO2 content on Figure 6 Shown in.

[0190] Table 6 shows the effect of the Sb2O5 content of the catalyst on the NOx conversion in the standard SCR reaction at 200° C. and in the fast SCR reaction at 300° C. in the new and aged state. The amounts of V2O5, WO3 and CeO2 were kept constant at 3.75 wt%, 1.00 wt% or 2.00 wt%, respectively, while the Sb2O5 content was varied from 0.00 wt% (VK2) to 2.75 wt% (K1), 4.00 wt% (K5) and 7.00 wt% (K6).

[0191] Table 6: Effect of Sb2O5 content on NOx conversion rate

[0192]

[0193] The results of the influence of Sb2O5 content on Figure 7 Shown in.

Claims

1. A method for preparing a catalyst, the catalyst comprising: • at least one oxide of vanadium in an amount of 2% to 6% by weight, • at least one oxide of tungsten in an amount of 0.5% to 2% by weight, • at least one oxide of cerium in an amount of 2% to 4% by weight, • at least one antimony oxide in an amount of 1% to 7% by weight, as well as • at least one oxide of silicon, and • Optionally, at least one oxide of molybdenum, at least one oxide of niobium, at least one oxide of zirconium, at least one oxide of tantalum and / or at least one oxide of hafnium; as well as • at least one titanium oxide as support material, the amount of which is measured so as to give a total of 100% by weight in each case based on the total weight of the catalyst and calculated as V2O5, WO3, CeO2, Sb2O5, TiO2, SiO2, MoO3, Nb2O5, ZrO2, Ta2O5 and / or HfO2; The method comprises: obtaining oxides of vanadium, tungsten, cerium, antimony, titanium, silicon and optionally oxides of molybdenum, niobium, zirconium, tantalum and / or hafnium, forming a mixture of said oxides, and The mixture is calcined.

2. The method according to claim 1, characterized in that The catalyst comprises at least one silicon oxide in an amount of 2% to 7% by weight, based on the total weight of the catalyst and calculated as SiO2.

3. The method according to claim 1 or 2, characterized in that: The oxides are provided in powder form.

4. The method according to claim 1 or 2, characterized in that: The mixture is a slurry of the oxide in water, and the method further comprises drying the slurry prior to calcining.

5. The method according to claim 1 or 2, characterized in that: In the mixture, a portion of the oxides are provided in the form of an aqueous solution.

6. The method according to claim 1 or 2, characterized in that: The mixture comprises oxides of tungsten, cerium, antimony, silicon and titanium which have been impregnated with an aqueous solution of a water-soluble vanadium compound.

7. The method according to claim 1 or 2, characterized in that: The mixture comprises oxides of vanadium, cerium, antimony, silicon and titanium which have been impregnated with an aqueous solution of a water-soluble tungsten compound.

8. The method according to claim 1 or 2, characterized in that: The at least two oxides in the mixture are provided in the form of one oxide being doped with the other oxide.

9. The method according to claim 1 or 2, characterized in that: The two or more oxides are provided in the mixture as a mixed oxide.

10. The method according to claim 1 or 2, characterized in that: The mixture comprises titanium dioxide doped with silicon dioxide and tungsten trioxide and impregnated with water-soluble compounds of vanadium, antimony and cerium.

11. The method according to claim 1 or 2, characterized in that: The mixture further comprises at least one oxide of molybdenum, at least one oxide of niobium, at least one oxide of zirconium, at least one oxide of tantalum and / or at least one oxide of hafnium.

12. The method according to claim 1 or 2, characterized in that: The amount of the at least one molybdenum oxide, the at least one niobium oxide, the at least one zirconium oxide, the at least one tantalum oxide and / or the at least one hafnium oxide is 0.5% to 20% by weight, based on the total weight of the mixture and calculated as MoO3, Nb2O5, ZrO2, Ta2O5 or HfO2.

13. The method according to claim 1 or 2, characterized in that: The method includes forming the mixture by dispersing titanium dioxide doped with 5 wt % silicon dioxide in water and adding vanadium dioxide, tungsten trioxide, cerium dioxide and antimony pentoxide thereto.

14. The method according to claim 13, characterized in that The added amounts of vanadium dioxide, tungsten trioxide, cerium dioxide and antimony pentoxide resulted in a catalyst composition comprising 86.00 wt% TiO2, 4.50 wt% SiO2, 3.75 wt% V2O5, 1.00 wt% WO3, 2.00 wt% CeO2 and 2.75 wt% Sb2O5.

Citation Information

Patent Citations

  • Process for producing a selectively reducing catalyst for flue gas denitrification and process for removing nitrogen oxides from flue gas using this catalyst

    DE112007000814T5

  • Catalysts for selective catalytic reduction denox technology

    EP0345695A2

  • Catalyst composition for selective catalytic reduction of exhaust gases

    US8975206B2

  • SCR catalyst for removal of nitrogen oxides

    US9662610B2

  • Vanadium / tungsten catalyst and process

    WO1989003366A1